Gender Analysis: Women's Involvement in Achieving Family Food Security through Climate Change Adaptation in the Coastal Areas of Padang City - Rinawati; henny, henny (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract This study analyzes women's involvement in ensuring family food security through climate change adaptation in the coastal areas of Padang City. Climate change significantly impacts food security, particularly for women who often play a frontline role in providing food for their families. Through urban farming practices, women can reduce their vulnerability to climate change by utilizing limited urban land to increase family food production.The study employs qualitative methods with a case study approach, including interviews, Focus Group Discussions (FGDs), and participatory observations to identify women's roles in climate change adaptation. The findings reveal that women's involvement in urban farming enhances family food security, strengthens the local economy, and improves community social networks. Urban farming training programs equip women with practical skills in sustainable agriculture, thereby reinforcing their roles in family food management. The study also emphasizes the importance of policies that integrate gender perspectives into climate change adaptation and food security strategies. Keywords: Adaptation, Food Security, Women, Climate Change, Urban Farming